Pengaruh Penggunaan Model Pembelajaran Air (Auditory, Intellectualy, Repetition) Terhadap Hasil Belajar Mata Pelajaran Matematika Pada Siswa Kelas IV SDN Nusa Tenggara - Jami Ahmad Badawi; Ratih Purnama Pertiwi; Sri Enggar Kencana Dewi (Jurnal Riset Madrasah Ibtidaiyah, 2022)
The main problem in this study is the learning process that still uses conventional methods, namely lectures and questions and answers, so that it affects the low motivation of students in learning, especially in mathematics subjects, this has an impact on low learning outcomes that have not reached the minimum completion criteria (KKM) of mathematics subjects. This type of research is quantitative research, this research is shown to test the theory through measuring variables with numbers and carrying out data analysis with statistical procedures. The purpose of this study is to find out how the use of the AIR Learning Model (Auditory, Intellectually, Repetition) affects the Learning Outcomes of Mathematics Subjects in Grade IV Students of SDN Nusa Tenggara. Research data were obtained by conducting observations, documentation, and interviews. To test whether there is an influence from the application of the AIR learning method, researchers conducted pre-tests and post-tests. The results of learning mathematics students before the material repetition method was applied, namely the average pre-test obtained an average score of 58.13 and after being given treatment the average score of the post-test was 86.20. From the results of the SPSS analysis, the paired test of the t-test sample obtained a significant value of 0.000 > 0.05 which means that there is an increase in the learning outcomes of the experiment class from the pre-test and post-test.